1976
DOI: 10.1093/jnci/57.6.1355
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Tumor Growth In Vivo by Antimacrophage Agents 2

Abstract: ABSTRACT-Various attempts were made to assess the role of the mononuclear phagocyte system in tumor resistance of rats in vivo. The growth of sc inoculated, weakly immunogenic, carcinogen-induced, syngeneic tumor cells was modestly reduced by ip injection and, more impressively, by local injection of peptoneinduced, activated, nonimmune macrophages. A single iv injection of silica particles or carrageenan on the day of sc tumor cell inoculation greatly enhanced tumor growth. When these agents had been given a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 23 publications
(30 reference statements)
7
50
0
Order By: Relevance
“…This observation has been previously reported for both chemically induced (Keller, 1976;Nelson & Nelson, 1978) and virally induced (Lotzova & Richie, 1977) tumours. It is unlikely that the enhancement is due to a direct stimulatory effect of carrageenan on tumour growth, since carrageenan has been shown to be toxic for tumour cells in vitro (Pollack & Nelson, 1973), although products from damaged macrophages may have an enhancing effect (Keller, 1976). Carrageenan has many biological effects (Di Rosa, 1972) including anticoagulant activity (Anderson & Duncan, 1965) and inhibition of complement (Borsos et al, 1965), all of which may affect tumour growth.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…This observation has been previously reported for both chemically induced (Keller, 1976;Nelson & Nelson, 1978) and virally induced (Lotzova & Richie, 1977) tumours. It is unlikely that the enhancement is due to a direct stimulatory effect of carrageenan on tumour growth, since carrageenan has been shown to be toxic for tumour cells in vitro (Pollack & Nelson, 1973), although products from damaged macrophages may have an enhancing effect (Keller, 1976). Carrageenan has many biological effects (Di Rosa, 1972) including anticoagulant activity (Anderson & Duncan, 1965) and inhibition of complement (Borsos et al, 1965), all of which may affect tumour growth.…”
Section: Methodssupporting
confidence: 87%
“…Carrageenan is known to impair delayed hypersensitivity reactions in vivo (Bice et al, 1971;Schwartz & Leskowitz, 1969) and is a potent immunosuppressant of antibody formation (Aschheim & Raffel, 1972;Thomson et al, 1976). Keller (1976) and Thomson & Fowler (1977) have shown that carrageenan has an enhancing effect on the growth of relatively large tumour-cell inocula. Benjamini et al (1977) reported that mitomycin C treatment of syngeneic tumour cells prevented replication of such cells, which could still be used to induce specific cell-mediated immunity.…”
mentioning
confidence: 98%
“…As effector cells from normal tissues are far more heterogeneous than peritonealexudate cells (Keller, 1976b), a role for effector cells other than mononuclear phagocytes capable of mediating spontaneous cytotoxicity also merits consideration. In view of the recently recognized diversity of the cell populations manifesting natural killer capacity, the demonstration of consistent abrogation of the cytolytic effector-cell activity in vitro by silica (Keller, 1973(Keller, , 1978, an agent accepted as selectively toxic for macrophages (Kessel, Monaco and Marchisio, 1963;Allison, Harington and Birbeck, 1966;Keller, 1976a) may not be entirely conclusive. It is therefore essential clearly to identify and characterize the mononuclear phagocytes from other cell types manifesting spontaneous killer capacity.…”
Section: Resultsmentioning
confidence: 99%
“…After culture at 37°C in a humid atmosphere of 5% C02 and 95% air in RPMI-1640 (Keller, 1976a;Keller, 1978).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation